Pengaruh Penyelenggaraan Supervisi Pendidikan Oleh Kepala Sekolah Terhadap Kompetensi Guru Sekolah Mnenengah Uumum Negeri di Kabupaten Jember: The Influence of Educational Supervision by School Principals on the Competence of Public Senior High School Teachers in Jember Regency - Mabfudz Siddiq (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2003)
The implementation of educational supervision by school principals remains a critical yet often problematic issue for improving teacher competence, particularly in developing regions. Grounded in behavioral, humanistic, and cognitive psychology, this study examines how directive, nondirective, and collaborative supervision approaches influence teachers’ professional, personal, and social competencies. The research aims to determine whether each approach significantly affects these three competency dimensions. A quantitative method was employed, with a sample of 80 participants (64 teachers and 16 principals) selected through quota sampling from 473 teachers across 16 state senior high schools in Jember. Multiple regression analysis using SPSS was conducted. The results reveal that, collectively, all three supervision approaches significantly influence teacher competencies. However, individually, the directive approach does not significantly affect professional and personal competencies; the nondirective approach shows no significant effect on any of the three competencies; and the collaborative approach significantly influences only social competence. The study concludes that while the simultaneous application of supervision approaches is beneficial, their standalone effectiveness varies. It is recommended that principals enhance collaborative strategies and provide teachers with more opportunities for professional development. Penyelenggaraan supervisi pendidikan oleh kepala sekolah masih menjadi isu krusial dalam peningkatan kompetensi guru, terutama di daerah berkembang. Berlandaskan psikologi behavioristik, humanistik, dan kognitif, penelitian ini mengkaji pengaruh pendekatan supervisi direktif, nondirektif, dan kolaboratif terhadap kompetensi profesional, personal, dan sosial guru. Tujuannya untuk mengetahui pengaruh masing-masing pendekatan terhadap ketiga dimensi kompetensi tersebut. Metode kuantitatif digunakan dengan sampel 80 orang (64 guru dan 16 kepala sekolah) dari 473 guru di 16 SMU Negeri di Jember melalui quota sampling. Analisis regresi berganda dengan SPSS menunjukkan bahwa secara bersama-sama ketiga pendekatan berpengaruh signifikan terhadap kompetensi guru. Namun secara parsial, pendekatan direktif tidak berpengaruh terhadap kompetensi profesional dan personal; pendekatan nondirektif tidak berpengaruh terhadap ketiga kompetensi; dan pendekatan kolaboratif hanya berpengaruh terhadap kompetensi sosial. Kesimpulannya, meskipun penerapan simultan bermanfaat, efektivitas masing-masing pendekatan bervariasi. Direkomendasikan agar kepala sekolah memperkuat supervisi kolaboratif dan memberikan ruang pengembangan profesional bagi guru.